DICTION USED IN SPOKEN LANGUAGE ON DONALD TRUMP’S SPEECH - Annafi Akbar Rozaq (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Diction or choice of words can produce a certain effect either orally or in writing and also Well-chosen words enhance a speaker's ability to pass a message clearly and easily. Poor word choice can cause message misinterpretation by the listeners. In this study, the researcher focused on analyzing the diction used in Donald Trump's speech. It is intended to be used as a reference or additional knowledge and can understand diction in spoken language. To support the research, the theory used diction. A speaker uses diction to communicate concepts that the audience can understand. Diction refers to a speaker's ability to explain simple and complex thoughts using precise and economical words that are appropriate for the intended audience. Researcher uses descriptive qualitative research is a type of scientific study that seeks specific information about a population's values, opinions, behaviors, and social context. Before being analyzed, the researcher used triangulation. In Donald Trump's victory speech, there were many informal diction terms used in spoken language. Because the situation and context when Donald Trump spoke in his victory speech were not appropriate, the appropriate one should use formal diction. It was supported in the formal situation of the president's victory speech. The result of this research indicated by using informal diction, Donald Trump with his speech caused a lot of controversies, provoked outrage, and many people did not like it.